(untitled) (The Research of Medical Science Review, 2025)
Background: Common dermatological issue causing poor quality of life for patients is acne scars. Scar look has been enhanced with several procedures including chemical peels and microneedling. The safety and effectiveness of 5% glycolic acid peel and microneedling in treating acne scars were compared in this study. Objectives: To assess and contrast for acne scar therapy the efficiency, patient satisfaction and side effects of 5% glycolic acid peel and microneedling. Methods: From November 2024 to February 2025, a cross-sectional study used a practical sample method, 184 patients in all with atrophic acne scars were enrolled. Two groups were formed from the participants: Group A had microneedling and Group B underwent treatment with 5% glycolic acid peel. Every group got four sessions of treatment separated three weeks apart. Reduction in scar grade (Goodman and Baron Scale), patient satisfaction (VAS scores), and subjective improvement in skin texture all helped to gauge efficacy. We noted negative outcomes including infection, hyperpigmentation and erythema. Results: Scar grades (1.7 ± 0.4) were considerably reduced in the microneedling group as opposed to the glycolic acid peel group (1.3 ± 0.3). Group A's (8.2 ± 1.1) patient satisfaction was higher than Group B's (7.5 ± 1.3). Approaching statistical significance (p = 0.07), Group A (78%) showed more subjective improvement in skin texture than Group B (65%). Though the variances were not statistically significant (p = 0.72), Group B had somewhat more adverse effects with higher frequencies of erythema (19% vs. 14%) and hyperpigmentation (16% vs. 11%). Conclusion: With better scar improvement, patient satisfaction, and same safety, microneedling is more successful than 5% glycolic acid peel for treating acne scars. Particularly for deeper scar types, it is advised as a first- line treatment for moderate-to-severe acne scars.